About Mechanism of Antihemolitic Action of Chlorpromazine Under Posthypertonic Stress in Erythrocytes - Semionova, Ekaterina A.; Chabanenko, Elena A.; Orlova, Natalia V.; Zubov, Pavel M.; Shpakova, Natalia M. (Problems of Cryobiology and Cryomedicine, 2017)
The research was performed to reveal an antihemolytic effect of chlorpromazine (CPZ) under post-hypertonic stress (PHS) of human erythrocyte depending on the substances present at different stages of experiment (pre-treatment, dehydration, rehydration) as well as the effect of CPZ on the redistribution of phosphatidylserine in erythrocyte membrane bilayer. It has been shown that pre-treatment of erythrocytes with CPZ at a concentration of 180 mmol/l did not lead to antihemolytic effect of the substance under PHS of erythrocytes. It has been established that CPZ under concentration of 100-300 mmol/l did not cause a transbilayer redistribution of phosphatidylserine molecules in erythrocyte membranes. Protective effect of CPZ was implemented following transfer of the cells from the dehydration medium (1.75 mol/l NaCl) into rehydration one (0.15 mol/l NaCl), containing CPZ, i. e.at the moment of stress action. Consequently, the mechanism of antihemolytic action of CPZ under PHS of erythrocytes was associated with the membrane reorganization during an incorporation of the substance molecules into it. Probl Cryobiol Cryomed 2017; 27(3): 219–229